A new MPPT method for PV array system under partially shaded conditions - Parlak, Koray Sener; Can, Hayrettin (My University, 2012)
Maximum power point tracking (MPPT) algorithms are among the most important research topics related to photovoltaic (PV) systems. Conventional MPPT methods yield effective results that are easy to perform under uniform irradiation conditions. However, as more than one local maxima is formed under partial shading conditions, these methods fall short of being successful. Even though there are MPPT methods cited in the literature that work accurately under these conditions, they are dependent on complex calculations or panel parameters. This study proposes a new method that finds the real MPP of the PV array under partially shaded conditions. This method is based on the principle of scanning the P-V curve obtained by sensing the current and voltage values of a capacitor connected to the output of the PV array within charging time. The proposed method was tested in the Matlab-Simulink environment, in a simulation performed under partially shaded conditions and successful results were obtained. © 2012 IEEE.
2012 3rd IEEE International Symposium on Power Electronics for Distributed Generation Systems, PEDG 2012 -- 25 June 2012 through 28 June 2012 -- Aalborg -- 92893
Keywords: maximum power point tracker; partial shaded conditions; photovoltaic panels